Relationship between negative maternal parenting style and social-emotional development of young children from urban lowincome households in Lembah Klang, Malaysia - Khairuddin, Laili Harlina; Madon, Zainal; Arshat, Zarinah (Human Resources Management Academic Research Society, 2024)
Negative parenting styles are known to correlate with more challenges in social-emotional development of children. Early emergence of challenges in social-emotional development, such as difficulties in regulating emotions and forming healthy social relationships during childhood, often persists into later years and is associated with various adverse outcomes. Hence, the present study aims to determine the relationship between maternal negative parenting style and social-emotional development, as well as differences in social-emotional development between male and female young children from low-income households in Lembah Klang, Malaysia. Using a cluster sampling method, 360 mothers of young children (aged 3 to 4 years old) were selected for this study. The Parenting Styles and Dimensions Questionnaire (PSDQ) Short-Form was used to assess negative maternal parenting styles, while the Ages and Stages Questionnaires: Social-Emotional (ASQ) measured social-emotional development. The findings indicated that children whose mothers exhibited higher levels of negative parenting styles tended to display more challenges in social-emotional development. Additionally, results also revealed that boys presented with more challenges in social-emotional development than girls. In conclusion, the present study suggests that negative parenting styles adopted by mothers may contribute to greater challenges in children's overall social-emotional development, with boys being particularly vulnerable to these effects. Furthermore, the findings highlight the need for improvement for parental education programs and targeted interventions particularly for boys.